(3GNJUGQ afhf GdCafGf aj Ydhe GdbQBfs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3bGd GdTjN Hf GdLhRi deG PcQJ ai cJGHi GdeSei Hafhf GdCafGf ai Ydhe GdbQBf ef GdeJTGHg ai afhf CMHHJ Cf CPcQgG gGgfG ef GdeTJHg Yjhfg ai aJM HGH GdCTcGd s
(3BNQgG (B:s
(3ShQI GdHQhL ajgG Pdc GdahR GdcHjQ hHGbi GdbQBf GdahR GdYXje agPG eNJUQ ef Yjhf eJTGHg GdbQBf Jcai ai JPcQI GdMGaX hEPG CQOJ GdHSW aYdjc Hafhf GdCafGf Je HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdeLGejYs